Political Islam and the State in Africa: By Hussein Solomon, Akeem Fadare, and Firoza Butler, eds. (Pretoria: Centre for International Political Studies (University of Pretoria), 2008. 260 pages.) (American Journal of Islam and Society, 2009)
Political Islam has been under the scholarly spotlight for over two decades.The events in the Muslim heartlands and beyond have caused scholars tocritically investigate the relationship between religion and politics throughoutthe era of secularism; some arguing that religion is on its way out, andothers stating that it is gradually gaining ground in the public arena. For thewestern-trained scholar, the religion-politics divide is a sine qua non; however,for those outside the scholarly circles, religion has always been connectedto and intertwined with politics. This has been the case with Islam.The editors of this text, which focuses on the nature of political Islam andthe nation-state on the African continent, have brought together a crop ofscholars with divergent views. It consists of nine chapters, an introductioncoauthored by Hussein Solomon and Akeem Fadare, and a conclusion coauthoredby Solomon and Firoza Butler ...